MORPHOLOGY AND MOLECULAR CHARACTERIZATION OF TOMATO LEAF MINER TUTA ABSOLUTA DIAGNOSED IN DUHOK GOVERNORATE / IRAQ - Mirza, Mohammed Saeed; Al-Muffti, Shamal Abdullah (Science Journal of University of Zakho, 2024)
Tomato leaf miner Tuta absoluta (Meyrick) is a highly destructive and invasive pest affecting tomato and other Solanaceae crops, causing severe economic damage. A comprehensive investigation into the presence of the tomato leaf miner T. absoluta was undertaken in this study via a field survey across tomato cultivation zones throughout all districts of Duhok Governorate in the Kurdistan Region of Iraq from July to September 2022. Instances of T. absoluta infestation were documented in Zakho, Amadiya, Summel, Dohuk, Shekhan, Aqrah, and Bardarash districts. The collected moths were described morphologically depending on the phenotypic characteristics and features of the male genitalia; the phallus was cylindrical; the valva was weakly curved and covered with long setae. The apex of the uncus extends almost to the tip of the valve. They were also confirmed at the molecular level through PCR analysis using mitochondrial cytochrome c oxidase subunit I (COI) as a molecular marker. The sequences of the mtCOI gene of T. absoluta specimens were analyzed and compared with the available COI sequence data members from GenBank. All studied specimens of T. absoluta were clustered together in a single group with a high support value, suggesting the presence of high homogeneity in the T. absoluta specimens. This work represents the first attempt at molecular identification of obtained specimens of T. absoluta in Iraq.